Response of a subalpine grassland to simulated grazing: aboveground productivity along soil phosphorus gradients - Thiel-Egenter, C.; Risch, A. C.; Jurgensen, M. F.; Page-Dumroese, D. S.; Krüsi, B. O.; Schütz, M. (Community ecology, 2007)
Interactions between grassland ecosystems and vertebrate herbivores are critical for a better understanding of ecosystem processes, but diverge widely in different ecosystems. In this study, we examined plant responses to simulated red deer (Cervus elaphus L.) grazing using clip-plot experiments in a subalpine grassland ecosystem of the Central European Alps. We measured aboveground net primary production (ANPP) and phosphorus (P) concentration of leaf tissue from plants of two vegetation types with different grazing history. The experimental plots were placed on a soil-P gradient and subject to two different clipping treatments, which simulated moderate and heavy grazing, respectively. We found distinct differences in the response of both ANPP and P concentration in leaf tissues in the two vegetation types. Compared to moderate, heavy grazing simulation did not affect ANPP in the vegetation type adapted to grazing, but decreased ANPP in the non-grazing adapted vegetation type. High soil-P levels also had different effects on the response of the vegetation to clipping in the two vegetation types with different grazing history. ANPP correlated positively with soil-P in non-grazing adapted tall-grass vegetation, while in grazing adapted short-grass vegetation a positive relationship between soil-P and the P concentration in leaf tissues was found. Our experiments provide data for a better understanding of ecosystem processes in high-elevation grasslands of the Alps with possible implications for both nature conservation purposes in protected areas and the management of agriculturally used grasslands.